Pengaruh Relaksasi terhadap Penurunan Tekanan Darah pada lansia Hipertensi: Tinjauan Sistematik - Safaruddin; Cristina, Tri Yahya; Andika, I Putu Juni; Sriwiyati, Lilik; Sapta, Monika Wulan (LPPM Hang Tuah Pekanbaru, 2025)
Hypertension is a condition characterized by elevated blood pressure above 140/90 mmHg, which can lead to serious health problems, particularly heart disease. Managing hypertension in the elderly requires effective health strategies, especially non-pharmacological treatments, to control its impact. This study aims to review the effect of relaxation on lowering blood pressure in elderly individuals with hypertension. The method used was PRISMA (Preferred Reporting Items for Systematic Review and Meta-Analysis), and relevant articles were searched through three databases: PubMed, Google Scholar, and ScienceDirect. A total of 1234 articles were initially identified, but after screening based on specific criteria, only 10 articles met the requirements for the literature review. Overall, relaxation had a positive impact on elderly individuals with hypertension. This systematic review found evidence that relaxation techniques are an effective non-pharmacological method to reduce blood pressure and stress in hypertensive elderly individuals, and they also help improve quality of life by better managing blood pressure and reducing physical and psychological burdens.